Philipp Melanchthon Die denker, leermeester en opvoeder van die Reformasie - van Wyk, Ignatius W.C. (Natie) (HTS Religion & Society Series, 2022)
Philipp Melanchthon (1497-1560) was, with Martin Luther, the most influential reformer of the church during the 16th century. He was also a reformer of university education, especially theological studies, as well as the school system in Germany. He was responsible for a theological curriculum that included Greek, Hebrew, and philosophy. He, as a professor of Greek at the University of Wittenberg since 1518, was the author of the first generally accepted Protestant confession, known as the Confessio Augustana (1530). He also wrote the first Protestant commentaries on Paul's letter to the Romans (1519), as well as the first Protestant handbook in systematic theology (1521). He was the main negotiator of the Protestant movement during the diets and religious discussions with the Roman Catholic Church. He is known as the 'teacher of Germany and Europe' and is respected as the father of the ecumenical movement. Yet, Melanchthon is not known to South Africans and especially Afrikaans-speaking people who, traditionally, have close links with the reformational tradition. There is not yet one single publication on Melanchthon in Afrikaans or by a South African scholar, making this book, therefore, the first by an Afrikaans-speaking scholar on Melanchthon.